PRACTICE RELATED TO OCCUPATIONAL HEALTH AND SAFETY AMONG WORKERS OF BRICK FACTORIES AT BHAKTAPUR, NEPAL - Bahadur, Krishna Bahadur; Budhathoki, Anoj; Sushmita; Karki, Kshitij (International Journal of Research -GRANTHAALAYAH, 2018)
The purpose of this study was to find out the practice related to occupational health and safety among the brick factory workers. The study was based on descriptive cross sectional design. Random proportionate sampling technique was applied to select the respondent from each randomly selected five brick factory. The total numbers of 300 samples of brick factory workers were selected. Semi-structured questionnaire and observation checklist were used for data collection. Most of the participants had knowledge about occupational health and safety. Similarly about 54.7% of them use gloves, 25.3% use boot and 18% use mask as personal protective equipment. Majority of participants were aware about occupational hazard but their practice level of personal protective equipment is low for protecting themselves. So the practice of personal protective equipment should be encouraged in the brick factory for the promotion of occupational health and safety.